2005
DOI: 10.1158/1078-0432.ccr-05-0087
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Peroxisome Proliferator-Activated Receptor γ on Anoikis and Invasion of Squamous Cell Carcinoma

Abstract: Purpose: Peroxisome proliferator-activated receptor g (PPARg) plays a important role in various physiological functions.We examined whether PPARg is expressed in primary squamous cell carcinoma and lymph node metastasis and whether PPARg is a potential target for tumor therapy. Experimental Design and Results: A high-level expression of PPARg was observed in tumor cells of human primary squamous cell carcinoma, lymph node metastasis, and squamous cell carcinoma cell lines. Treatment with PPARg-specific antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(98 citation statements)
references
References 37 publications
4
91
0
3
Order By: Relevance
“…In the present study, the endogenous and exogenous PPAR-g ligands 15-PGJ 2 and ciglitazone, respectively, dose-dependently inhibited pancreatic cancer cell invasion, further supporting the notion of PPAR-g ligands as being potentially therapeutic agents in pancreatic cancer. There is now accumulating evidence that PPAR-g ligands possess potent anti-invasive properties in human cancers (29)(30)(31). Our findings that PPAR-g ligands decreased uPA and increased PAI-1 levels in pancreatic cancer cells, thereby substantially reducing overall urokinase activity, strongly suggested that the anti-invasive properties of PPAR-g ligands were mediated by modulating the plasminogen activator system.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, the endogenous and exogenous PPAR-g ligands 15-PGJ 2 and ciglitazone, respectively, dose-dependently inhibited pancreatic cancer cell invasion, further supporting the notion of PPAR-g ligands as being potentially therapeutic agents in pancreatic cancer. There is now accumulating evidence that PPAR-g ligands possess potent anti-invasive properties in human cancers (29)(30)(31). Our findings that PPAR-g ligands decreased uPA and increased PAI-1 levels in pancreatic cancer cells, thereby substantially reducing overall urokinase activity, strongly suggested that the anti-invasive properties of PPAR-g ligands were mediated by modulating the plasminogen activator system.…”
Section: Discussionmentioning
confidence: 65%
“…Cells were maintained in DMEM containing 10% fetal bovine serum (FBS) at 37˚C under 0.5% CO 2 . For the cell growth experiment, cells were trypsinized and replated onto culture dishes (11)(12)(13)(14)(15)17,18). SCC cells were counted using a Countess Automated Cell Counter (Invitrogen, Eugene, OR, USA).…”
Section: Antibodiesmentioning
confidence: 99%
“…Therefore, increased FABP4 expression may affect the growth of various tumor types. Our research group also reported that molecules controlled by peroxisome proliferator-activated receptor γ (PPARγ) play key roles in SCC growth (11)(12)(13)(14)(15). As FABP4 is known to mediate transcription with PPARγ (4,16), we hypothesized that FABP4 may regulate SCC growth.…”
Section: Introductionmentioning
confidence: 97%
“…3-(4,5-dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium bromide assay was processed as described previously (20). For Western blot assay, cells were allowed to adhere to FN-coated plates for 2 h, and then proteins were collected.…”
Section: Transfection and Selection Of Stably Transfected Hepg2/ Mr-1mentioning
confidence: 99%